INVESTIGAÇÃO EPIDEMIOLÓGICA E ETNOFARMACOLÓGICA EM MULHERES COM SINTOMAS VULVOVAGINAIS EM UM MUNICÍPIO DA BAIXADA MARANHENSE - LEITE, Alanna Mylla Costa (2026)
Introduction: Vulvovaginal symptoms such as vaginal discharge, pruritus, burning, dysuria, and genital discomfort are frequent complaints in healthcare services and may result from different infectious and non-infectious conditions, including bacterial vaginosis, fungal infections, sexually transmitted infections, hormonal changes, and irritative processes. Among infectious causes, vulvovaginal candidiasis stands out, traditionally associated with Candida albicans. The increasing resistance to antifungal and antibacterial agents has driven the search for alternative therapies, including probiotics and plant-derived compounds, reinforcing the relevance of local ethnopharmacological knowledge. Objective: To investigate the epidemiological and ethnopharmacological profile of women with vulvovaginal symptoms receiving care in health services in a municipality of the Baixada Maranhense, with a focus on vulvovaginal candidiasis, analyzing prevalence, clinical manifestations, associated factors, and preventive and therapeutic practices adopted. Methods: This is an analytical cross-sectional epidemiological study conducted between October 2024 and August 2025, including women aged 18 to 50 years attending Primary Health Care Units and a hospital in the municipality of Pinheiro, Maranhão, Brazil. A structured questionnaire covering sociodemographic, clinical, and ethnopharmacological variables was applied. Data were analyzed using Jamovi software, employing chi-square and Fisher’s exact tests (p < 0.05). The study was approved by the Research Ethics Committee of the Federal University of Maranhão (Opinion No. 7,163,938). Results: A total of 153 women attending health services in Pinheiro, Maranhão, were evaluated. The prevalence of laboratory detection of Candida spp. was 8.5%, including single and mixed infections. A discrepancy was observed between self-reported symptoms, such as vaginal discharge and pruritus, and laboratory confirmation. Lower educational level, vaginal douching, and continuous medication use were associated with the detection of Candida spp. The use of medicinal plants was reported by 50.3% of participants, especially among women with recurrent symptoms. Aroeira, barbatimão, and cat’s claw were the most frequently cited species, generally used in homemade preparations and associated with a high perception of symptom improvement. Conclusion: Vulvovaginal candidiasis showed low laboratory prevalence compared to the high frequency of vulvovaginal symptoms, highlighting challenges in the clinical recognition of vulvovaginitis in primary care. Clinical, behavioral, and social factors influenced the occurrence of infection, while the widespread use of medicinal plants underscored the relevance of ethnopharmacological practices in women’s therapeutic pathways. These findings point to the need for integrated strategies that combine qualification of care, health education, and critical recognition of traditional knowledge in women’s healthcare within the Brazilian Unified Health System (SUS).